Nutrient cycling efficiency and water requirement of various catch crops under varying climatic conditions - Selzer, Tabea; Justus Liebig University Giessen (My University, 2023)
In the face of climate change and other challenges of modern agriculture, catch and cover crops (CCC) have gained importance for our agroecosystems. However, catch and cover cropping has its own challenges. Two of those challenges, namely (a) the nutrient cycling efficiency and (b) the water requirement of CCC were investigated in this thesis. Specifically, (1) the maximum nutrient uptake under non-limiting growth conditions as an indicator for nutrient cycling efficiency was determined and (2) relevant water inputs (rainfall, irrigation, and occult precipitation) and water losses (transpiration, evaporation, and leaching) were quantified in container experiments. Seven different CCC were cultivated as pure stands and as a mixture in comparison to a bare fallow under semi-controlled conditions in 2020 and 2021. Furthermore, the model AMBAV by the German Meteorological Service was used to simulate evapotranspiration (ET) for three of the CCC. The simulated data were compared with measured data obtained in the container experiments. (1) Nutrient cycling efficiency. Catch and cover crops with the highest biomass also had the highest N, P, and K uptake. Phacelia showed the highest potential for conservation of all three nutrients, although the low C : N ratio of the frost-sensitive catch crop could promote nutrient losses during winter. A clear differentiation of CCC ideotypes for N, P, and K uptake was not possible. However, a general relationship between nutrient uptake and increasing root surface area as well as root length density was established. In addition, it was shown that pure stands can be as efficient as a CCC mixture in terms of nutrient retention. (2) Water requirement of catch and cover crops. Although favorable conditions occurred during both vegetation periods, no evidence of occult precipitation was found. In autumn, soil water was depleted by fast-growing CCC with high biomass production in comparison to a bare fallow. During winter, soil water was recharged in the treatments with frost-sensitive CCC due high winter precipitation, while in early spring rising temperatures increased transpiration losses of a winter-hardy cover crop, leading to a reduction of soil water. Whether CCC deplete or conserve soil water is dependent on (a) climate, (b) soil type, and (c) management. From a water-budget viewpoint, the cultivation of CCC is neither economically nor agronomically feasible in (semi-)arid regions / in dry years. Effective management options for water conservation in regions where catch and cover cropping are feasible are (a) the early termination of CCC growth, (b) no tillage, and (c) the preparation of a mulch layer or (d) the cultivation of frost-sensitive CCC which form a natural mulch in winter. However, management practices which are beneficial from a water-budget viewpoint can have negative impacts on the nutrient cycling efficiency. A legislative framework which distinguishes between the aims of CCC cultivation in (semi-)arid regions / dry years and humid regions / wet years is proposed and challenges for such a framework are identified. It was shown that simulations of ET with the model AMBAV severely underestimated measured ET. Further optimization of the model is needed for the reliable prediction of CCC water requirement. Moreover, simulations should be made with site-specific data instead of default data. An optimized version of AMBAV which reliably predicts water fluxes of CCC could become an effective tool for farmers’ water management decisions.
Keywords: cover crops; catch crops; nutrient cycling; evapotranspiration; mulch; water use efficiency; sensitivity analysis; ddc:500